Drivers of customer satisfaction with waste-disposal-services: A PLS-SEM approach - Torsten Mischel; Svenja Damberg (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Prior studies on customer satisfaction research have focused on the private sector. However, few studies have looked at services of general interest. Methodology: Using a PLS-SEM methodology, we establish and adapt a theoretical model based on the well-known ECSI to the waste disposal service context and use a sample of 2062 responses to assess our results. Findings: Our results show that disposal performance is most important in explaining customer satisfaction, followed by price-performance-ratio and service hotline performance. Originality: For this study, we adapted a well-established model and extended it with the construct 'waste disposal performance'. We conducted expert interviews and tested the extended model in pretests before final data collection. We show that this construct is the most important driver for customer satisfaction in the context of waste disposal services. Research limitations: The data have been collected using self-reported questionnaires in Germany. Future studies should collect longitudinal data and test the model in other countries. Managerial implications: The most important implication of our study is that managers of waste disposal services should focus on the logistical aspects behind their services, such as timely disposal of waste to ensure customer satisfaction.
urn:nbn:de:gbv:830-882.0161907; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Business Analytics